Exogenous Melatonin Application Enhances Rhizophagus irregularis Symbiosis and Induces the Antioxidant Response of Medicago truncatula Under Lead Stress - Zhang, Xiangyu; Zhang, Huijuan; Zhang, Haoqiang; Tang, Ming (Frontiers in Microbiology, 2020)
Melatonin is a new kind of plant growth regulator. The aim of this study was to figure out the effect of melatonin on arbuscular mycorrhizal (AM) symbiosis and heavy metal tolerance. A three-factor experiment was conducted to determine the effect of melatonin application on the growth, AM symbiosis, and stress tolerance of Medicago truncatula. A two-factor (AM inoculation and Pb stress) experiment was conducted to determine the effect of AM fungus on melatonin accumulation under Pb stress. AM plants under Pb stress had a higher melatonin accumulation than non-mycorrhizal (NM) plants under Pb stress. Acetylserotonin methyltransferase (ASMT) is the enzymatic reaction of the last step in melatonin synthesis. The accumulation of melatonin may be related to the expression of MtASMT. Melatonin application increased the relative expression of MtPT4 and AM colonization in AM plants. Melatonin application decreased Pb uptake with and without AM inoculation. Both melatonin application and AM inoculation improved M. truncatula growth and increased antioxidant response with Pb stress. These results indicated that melatonin application has positive effects on AM symbiosis and Pb stress tolerance under Pb stress. AM inoculation improve melatonin synthesis capacity under Pb stress. Melatonin application may improve AM plant growth by enhancing AM symbiosis, stimulating antioxidant response, and inhibiting Pb uptake. response of M. truncatula.